ILRI's strategy for livestock development in Asia - Wright, Iain A. (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Iain Wright reflects on ILRI's research in Asia.